Perancangan dan Analisa Sistem Perpipaan Pompa Sertifugal P.100/15 pada Unit Kilang Cepu - Indra Adi Gunawan; M arif; Donny Albari; Zain Lillahulhaq; Syamsuri Syamsuri; Anindya Rachma Dwicahyani (Institut Teknologi Adhi Tama Surabaya, 2021)
A centrifugal pump is a pump that works on the principle of increasing fluid pressure by increasing speed through centrifugal force. The application of pumps is mostly carried out in the industrial sector to deliver fuel, air and other multi-phase fluids. The design of the pump must be adjusted to the layout of the piping system through which the fluid flows and consider the height of the pipe at the pump. In this research, the design and analysis of the piping system on the P.100/15 Sertifugal Pumps at the Cepu Refinery Unit was carried out. This research involved the mayor and minor losses in the piping system. In addition, the calculation of power in the piping system is also carried out. From the calculations made, the total head is 17.403 m with a pump power of 1.7 kW.